Tuvalu : 2010 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Tuvalu. (IMF Staff Country Reports; Country Report ;, 2011)
Recent economic developments of Tuvalu were discussed. Major construction projects to build a wharf and a power station have been completed, and seafarer employment-Tuvalu's main foreign exchange earning source for the private sector-is weak. The Consolidated Investment Fund (CIF) available for budget financing will be depleted. Freezing wages and reducing travel costs will also be important. Improvements in the banking sector and credit culture will help to support private-sector development. Executive Directors agreed to ensure fiscal sustainability.